Debit Card Adoption Attributes and Customer Satisfaction: A Study on Dutch-Bangla Band Ltd. - Mynuddin, Md (Journal of Business and Technology (Dhaka), 2017)
Dutch-Bangla Bank Ltd (DBBL) is one of the most innovative and technologically advanced banks. It stands as a leader in the country's banking sector. Recently it was found that a large number of customers were using debit card for various purposes like convenient, speedy money transaction, easy maintenance etc. To assess which factors were related to debit card adoption, a questionnaire was developed. The survey was conducted among 239 customers from three different branches of Sylhet city. The study showed the significantly influencing debit card adoption factors, which were transaction transparency, shopping through Point-of-Sell (POS) utility bill payment, easiest way to maintain relationship with bank community and so on. Journal of Business and Technology (Dhaka) Vol.11(1-2) 2016; 129-140